2011
DOI: 10.1021/la2025846
|View full text |Cite
|
Sign up to set email alerts
|

Are Hydrotropes Distinct from Surfactants?

Abstract: The physicochemical properties of a homologous series of sodium p-n-alkylbenzoates have been investigated. The objective was to determine whether there is a clear transition point from hydrotropic to surfactant-like behavior with increasing alkyl chain length n, so as to shed clear light on the aggregation mechanism of so-called "hydrotropes". Electrical conductivity measurements were used for a first estimation of the critical aggregation concentrations (cac). As for classical surfactants, log(cac) depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
110
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 38 publications
15
110
0
Order By: Relevance
“…Sodium octanoate, sodium heptanoate, sodium hexanoate and sodium benzoate were purchased from Aldrich and used as received. Sodium cyclohexanoate was prepared from its parent acid (also purchased form Aldrich at the highest purity available) as described elsewhere [20]. The momentum transfer Q is defined as:…”
Section: Methodsmentioning
confidence: 99%
“…Sodium octanoate, sodium heptanoate, sodium hexanoate and sodium benzoate were purchased from Aldrich and used as received. Sodium cyclohexanoate was prepared from its parent acid (also purchased form Aldrich at the highest purity available) as described elsewhere [20]. The momentum transfer Q is defined as:…”
Section: Methodsmentioning
confidence: 99%
“…The details of surfactant synthesis, purification and characterization 7 have been described elsewhere. 21,22 The surfactants were used at constant molarity (0.017 8 mol L -1 in a 0.02 L cell), the hydrotropes were dissolved in water with mixed H2O and D2O at where θ is the scattering angle and λ the incident neutron wavelength. 16 The scattering data were normalized for the sample transmission, empty cell and solvent 17 background and put on an absolute intensity I(Q)/cm -1 scale using standard procedures, the 18 errors in intensity I(Q) are expected to be lower than 5%.…”
Section: Materials and Compositionsmentioning
confidence: 99%
“…16 In one of the very few reports on anisotropic self-assembled structures in scCO2, it was 17 found that by exchanging the surfactant counter ion Na + with divalent species such as Co 2+ 18 and Ni 2+ , a sphere-rod shape transition can be obtained for the micelles formed not only in 19 alkane solvents with hydrocarbon surfactants, 12 but also in scCO2. 4 However, the shape 20 transitions were only observed at very low water content with water: surfactant molar ratio 21 (W = [water]/[surf]) ≤ 10, and furthermore, micelles formulated by the counter-ion 22 exchanged surfactants generally require a relatively high pressures (~300 bar) to be 23 stabilised in scCO2. These factors have largely limited practical applications to modify scCO2 1 viscosity using this approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally similar to surfactants, hydrotropic salts can act as strong "binding" additives and reduce surface tension in an aqueous solution. A number of organic hydrotropic salts such as NaSal [Rehage and Hoffmann (1988a); Shikata et al (1987)], SHNC [Mendes et al (1997[Mendes et al ( , 1998], p-toluene sulfonate [Soltero et al (1996)], chlorobenzoate [Carver et al (1996)], and naphthalenesulfonate [Brown et al (1989)] have been studied in combination with cationic surfactants because these mixtures can reduce the charge density of surfactant micellar aggregates significantly, enhancing ion pairing and surface activity of the micelles above a minimum hydrotropic concentration (MHC), promoting growth of wormlike micelles at a much lower salt/surfactant ratio in comparison to other salts [Hatzopoulos et al (2011); Hodgdon and Kaler (2007); Lin et al (2012); Subramanian et al (2013)]. In addition, Schubert et al (2003) reported that adding the hydrotropic salt NaTosylate (0.25 wt.…”
Section: Introductionmentioning
confidence: 99%